2013
DOI: 10.1590/s0034-8910.2013047003428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de tracoma entre escolares brasileiros

Abstract: OBJECTIVE:To estimate the prevalence and describe the distribution of trachoma among schoolchildren in Brazilian municipalities. METHODS:Cross-sectional study, using cluster sampling, of the schoolchildren population of the Brazilian municipalities with Human Development IndexMunicipal lower than the national average. This trachoma prevalence survey was conducted by the Ministry of Health, in the period [2002][2003][2004][2005][2006][2007]. There were 119,531 schoolchildren selected from 2,270 schools located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
4
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 12 publications
2
21
4
14
Order By: Relevance
“…On the other hand, a household survey carried out with children in the community of Vila Estrutural, a former invasion area in the Brazilian Federal District and under precarious conditions of sanitation, demonstrated a prevalence of 12.5% (15) , wheras in the studies of Lucena et al (16) in Porteira (CE), a rate of 26.2% was observed. Lopes et al (17) found cases of trachoma in all Brazilian States, but reported an average prevalence of 6.1% in Santa Catarina, 4.6% in Rio Grande do Sul and 4.5% in Roraima. According to these authors, in MG the average prevalence was 4.8%.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a household survey carried out with children in the community of Vila Estrutural, a former invasion area in the Brazilian Federal District and under precarious conditions of sanitation, demonstrated a prevalence of 12.5% (15) , wheras in the studies of Lucena et al (16) in Porteira (CE), a rate of 26.2% was observed. Lopes et al (17) found cases of trachoma in all Brazilian States, but reported an average prevalence of 6.1% in Santa Catarina, 4.6% in Rio Grande do Sul and 4.5% in Roraima. According to these authors, in MG the average prevalence was 4.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Embora bastante prevalente em nosso meio (Silva, 2014;Jesus et al, 2013;Lopes et al, 2013;Lucena;Cavalcanti, 2010;Lopes, 2008;Paula;Medina;2002), o…”
Section: Resultsunclassified
“…A face interna das pálpebras e a esclera são recobertas por uma membrana fina e transparente chamada conjuntiva (Fig.1B) (JESUS et al, 2013;LOPES et al, 2013;DANTAS, 2013;MACHARELLI et al, 2013;CANINÉO et al, 2012;SCHELLINI et al, 2010;FERRAZ et al, 2010;LUCENA;CAVALCANTI et al, 2010 ;LOPES, 2008;ALMEIDA, 2007;KOIZUMI et al, 2005 De acordo com Thylefors et al (1987) o tracoma apresenta cinco formas clássicas (Fig.3) Certamente alcançar este objetivo seria de grande importância no combate a esta bactéria. Foram considerados todos os trabalhos publicados no período.…”
unclassified
“…Not observed natural or acquired immunity to infection. Some experimental studies show that there is some resistance after the first episode of infection, but a partial resistance because after a new inoculation, a new infection is developed [9,24].…”
Section: Pathophysiologymentioning
confidence: 99%